Decoding and comprehension skills mediate the link between a small‐group reading programme and English national literacy assessments. (10th July 2021) - Vousden, Janet I.; Cunningham, Anna J.; Johnson, Helen; Waldron, Sam; Ammi, Sabrina; Pillinger, Claire; Savage, Robert; Wood, Clare
Abstract : Background: Despite the fact that literacy instruction is a main focus of primary education, many children struggle to meet nationally set standards. Aims: We aimed to test which components of a comprehensive reading programme (ABRACADABRA: https://eur03.safelinks.protection.outlook.com/?url=https%3A%2F%2Fdoi.org%2F10.1186%2FISRCTN18254678&data=04%7C01%7Cjanet.vousden%40ntu.ac.uk%7C880280e0b00749df855308d94068a0bb%7C8acbc2c5c8ed42c78169ba438a0dbe2f%7C1%7C0%7C637611640381216902%7CUnknown%7CTWFpbGZsb3d8eyJWIjoiMC4wLjAwMDAiLCJQIjoiV2luMzIiLCJBTiI6Ik1haWwiLCJXVCI6Mn0%3D%7C1000&sdata=%2B4U9sGfofkyCPEY7lWz8n3TPoMOAeJMXyFwdhW6EpUw%3D&reserved=0) mediated the effect of the programme on nationally assessed literacy outcomes. Sample: Following blind allocation, 516 Year 1 pupils from 40 schools were randomized to the programme group, and 908 Year 1 pupils, to a control condition. Methods: Pupils in the programme completed 20 weeks of instruction in grapheme/phoneme knowledge, decoding, and comprehension. Control children received regular classroom instruction. Results: Children in the programme group were significantly better at these taught skills after the programme finished (effect sizes: grapheme/phoneme knowledge, β = .33, 95% CI [0.09–0.57]; decoding, β = .26, 95% CI [0.09–0.43]; and comprehension, β = .26, 95% CI [0.05–0.47]). Improvements in the programme group's decoding and comprehension skills fully mediated the improvements in national literacy assessments serving as a delayed post‐test 12 months after the programme. Programme group pupils were 2.3 (95% CI [1.4–4.1]) times more likely to achieve/exceed the expected standard in reading, and 1.8 (95% CI [1.2–2.6]) times more likely to achieve/exceed the expected standard in writing due to an increase in the trained skills. Conclusions: These results provide strong evidence that a programme that incorporates decoding and comprehension instruction for typically developing beginning readers improves distal educational outcomes in reading and writing through increasing proficiencies targeted by the reading programme.